(untitled) (Research, Society and Development, 2022)
This work is the result of exploratory and descriptive research, with quantitative nature of data, which aimed to investigate the knowledge of high school students in southern Brazil about aspects related to Paleontology in general and, more specifically, to the basic concepts of Molecular Paleontology. The sample group consisted of 52 high school students of 2nd grade from two private schools located in the municipalities of Araucária (PR) and Palhoça (SC), southern Brazil. Data were obtained through a structured online questionnaire, prepared via the Google Forms platform, consisting of 21 objective multiple-choice questions. The analysis of the questions was performed using descriptive statistics to examine the frequency of responses distributed in the three categories of analysis: 1) socioeconomic characteristics, 2) general knowledge about Paleontology and 3) specific knowledge about Molecular Paleontology. The results demonstrate that the students’ answers on basic concepts of Molecular Paleontology are consistent with the data available in the scientific literature, which demonstrates that high school students are able to acquire and apply complex contents related to molecular biology, fossils, and evolution in a school environment. Since there are few studies that sought to investigate the understanding of basic education students about Paleogenomics and Paleoproteomics subjects, it is clear that the data presented here may fill a gap in the existing knowledge in our country.